Analisis Zona Klasifikasi Iklim Oldeman untuk Kesesuaian Tanaman Padi (Oryza sativa L.) di Kabupaten Lampung Timur - Amalia Agustin; Muhammad Amin; Ridwan Ridwan; Ahmad Tusi (Jurnal Agricultural Biosystem Engineering, 2022)
Climate change is a change that occurs in the pattern of climate elements that are different from previous conditions. Climate change that occurs can lead to negative impacts on agriculture, namely the delay in starting planting time due to changeable weather not in accordance with forecasts until the problem of crop failure. East Lampung Regency is a regency that has the second largest agricultural land area in Lampung Province. Climate classification is the identification that is carried out to look for differences and determine the climate that occurs in a region. Climate identification can be done by monitoring changes in weather elements in a period of at least 10 years and at most 30 years. Oldeman's climate classification is to make climate types based on the number of wet months and dry months. The wet month category is the month that has rainfall >200mm and the dry month is with rainfall <100 mm. The purpose of this study was to determine the type of climate in East Lampung Regency based on oldeman climate classification, determine the right planting pattern for rice crops based on Oldeman climate classification, and determine the suitability of production and suitability of land for rice cultivation based on Oldeman climate classification. The method used in this study is the analysis of secondary data, namely rainfall for 10 years which is then interpolated with Geographic Information System applications. Based on the analysis results of East Lampung Regency has 6 types of climate, namely C1, C2, C3, D2, D3, and E3 with planting patterns applied in accordance with the oldeman climate classification. Suitability of land based on the type of climate obtained the results of 2 kinds of land types are very appropriate and marginal appropriate. While the suitability of rice production with climate classification East Lampung Regency has 13 districts that are appropriate and 4 districts are not appropriate. Sub-districts that are not suitable can be sought to have increased production results.